2007
DOI: 10.1021/ol702390p
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Double [2 + 2 + 2] Cycloaddition of 1,4-Bis(diphenylphosphinoyl)buta-1,3-diyne with Tethered Diynes:  A Modular, Highly Versatile Single-Pot Synthesis of NU-BIPHEP Biaryl Diphosphines

Abstract: Rhodium-catalyzed double [2 + 2 + 2] cycloaddition of 1,4-bis(diphenylphosphinoyl)buta-1,3-diyne with tethered diynes provides a straightforward, single-pot procedure for the synthesis of a new class of tropos biaryl diphosphine, NU-BIPHEP. This methodology represents a significant improvement on existing multistep procedures. Enantiopure Lewis acid platinum complexes of these diphosphines are highly efficient catalysts for carbonyl-ene and Diels-Alder reactions, and ruthenium diphosphine-diamine complexes cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The rhodium catalyzed double [2 + 2 + 2] cycloaddition of 1,4-bis(diphenylphosphinoyl)buta-1,3-diyne and a variable diyne compound is the key step in the preparation of “NU-BIPHEPs” [ 23 ] and related biaryls [ 24 ]. Doherty et al reported the use of various diynes yielding for instance tetrahydrobiindene 1a and N -tosyl-protected tetrahydrobiisoindole 1b as the only N -heterocyclic compound ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rhodium catalyzed double [2 + 2 + 2] cycloaddition of 1,4-bis(diphenylphosphinoyl)buta-1,3-diyne and a variable diyne compound is the key step in the preparation of “NU-BIPHEPs” [ 23 ] and related biaryls [ 24 ]. Doherty et al reported the use of various diynes yielding for instance tetrahydrobiindene 1a and N -tosyl-protected tetrahydrobiisoindole 1b as the only N -heterocyclic compound ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, introduction of functional groups which enable a modular derivatization approach is often hampered by long and tedious synthetic procedures. Doherty et al reported a rhodium catalyzed double [2 + 2 + 2] cycloaddition strategy for a convergent synthesis of “NU-BIPHEP”s [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… Synthesis of biaryl diphosphine oxides by cationic rhodium(I)/ rac ‐binap catalyzed double [2+2+2] cycloadditions 37…”
Section: Rhodium‐catalyzed Enantioselective [2+2+2] Cycloadditionsmentioning
confidence: 99%
“…The application of the double [2+2+2] cycloaddition approach to the synthesis of C 2 ‐symmetric biaryl phosphorus compounds was first reported by Doherty and co‐workers 37. They reported that the reaction of 1,4‐bis(diphenylphosphinoyl)buta‐1,3‐diyne ( 57 ) with terminal α,ω‐diynes 56 in the presence of a cationic rhodium(I)/ rac ‐binap catalyst furnished biaryl diphosphine oxides 58 in excellent yields (Scheme ) 37…”
Section: Rhodium‐catalyzed Enantioselective [2+2+2] Cycloadditionsmentioning
confidence: 99%
“…Although these approaches are now well established, a number of alternative and potentially practical synthetic methods have recently been developed that will extend the range of accessible architectures and substitution patterns and thereby create further opportunities for ligand discovery and optimization. In this regard, as part of an ongoing program to develop new, atomeconomical and efficient approaches for the synthesis of atropos and tropos diphosphines 40,41 , we have used rhodium-catalyzed [2 + 2 + 2] cycloaddition to construct the biaryl framework of 2,2′-bis(diphenylphosphino)biphenyl (BIPHEP)-type diphosphines from 1,4-bis(diphenylphosphinoyl)-buta-1,3-diyne and a selection of 1,n-tethered diynes 42 ; an asymmetric version of this reaction was subsequently applied to the synthesis of axial chiral biaryl diphosphines 43 and phosphonates 44 in exceptionally high enantioselectivity. Symmetrical and unsymmetrical tropos and atropos biaryl diphosphines have also been prepared via a stepwise and highly regioselective double Diels-Alder…”
Section: Introductionmentioning
confidence: 99%